2017
DOI: 10.1002/em.22104
|View full text |Cite
|
Sign up to set email alerts
|

Associations between arsenic (+3 oxidation state) methyltransferase (AS3MT) and N‐6 adenine‐specific DNA methyltransferase 1 (N6AMT1) polymorphisms, arsenic metabolism, and cancer risk in a chilean population

Abstract: Inter-individual differences in arsenic metabolism have been linked to arsenic-related disease risks. Arsenic (+3) methyltransferase (AS3MT) is the primary enzyme involved in arsenic metabolism, and we previously demonstrated in vitro that N-6 adenine-specific DNA methyltransferase 1 (N6AMT1) also methylates the toxic iAs metabolite, monomethylarsonous acid (MMA), to the less toxic dimethylarsonic acid (DMA). Here, we evaluated whether AS3MT and N6AMT1 gene polymorphisms alter arsenic methylation and impact iA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…More research is needed to understand the underlying mechanisms and pathways. It also remains to be elucidated whether the variations in selenium metabolism may influence the selenium status in terms of plasma selenium, expression and function of selenoproteins, and health effects of selenium intake (both low and high) as previously shown for arsenic through, for example, higher susceptibility to toxicity in individuals with higher percentages of MMA ( de la Rosa et al 2017 ).…”
Section: Discussionmentioning
confidence: 97%
“…More research is needed to understand the underlying mechanisms and pathways. It also remains to be elucidated whether the variations in selenium metabolism may influence the selenium status in terms of plasma selenium, expression and function of selenoproteins, and health effects of selenium intake (both low and high) as previously shown for arsenic through, for example, higher susceptibility to toxicity in individuals with higher percentages of MMA ( de la Rosa et al 2017 ).…”
Section: Discussionmentioning
confidence: 97%
“…An association has been reported between polymorphisms in the arsenic methyltransferase gene (AS3MT) and arsenic-related cancer risk. 42 Multiple studies have demonstrated that incomplete arsenic metabolism, with higher fractions of inorganic arsenic and methyl-arsenic acid and lower fractions of dimethyl-arsenic acid, is a marker for increased susceptibility to arsenic-related cancers. 5,43,44 The methylation of arsenic is thought to be one of the primary aspects of arsenic carcinogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is involved in converting the arsenic metabolite monomethylarsonous acid to the lesstoix dimethylarsonic acid (Ren et al, 2011 ; Zhang et al, 2015a ). N6AMT1 polymorphisms are reported to be associated with arsenic methylation (Harari et al, 2013 ; Chen et al, 2017 ; de la Rosa et al, 2017 ). N6AMT1 rs2254638 is a T to C substitution in intron, and the exact function of the SNP remains unknown.…”
Section: Discussionmentioning
confidence: 99%